The Effect of the Method of Preparation on the Textural, Acidic and Catalytic Properties of Chromia–Alumina Catalysts - Th. El-Nabarawy; L.B. Khalil; A. M. Youssef (Adsorption Science & Technology)
Pure alumina 'A' and chromia–alumina catalysts containing 25 mol% Cr 2 O 3 (IAC, IIAC and IIIAC) were prepared by impregnation, coprecipitation and coating techniques, respectively. The adsorption of nitrogen at 77 K and of benzene and water vapour at 308 K was determined. The chemisorption of pyridine at 400 K was measured and the surface acidities calculated. The conversion of 2-propanol and cracking of cumene were investigated using the pulse microcatalytic technique. Coating alumina with chromia causes considerable changes in the textural and adsorption properties, impregnation of alumina with chromia leads to smaller variations while coprecipitation gives intermediate changes in textural and adsorption properties. The same was found true for the surface acidities as determined by the chemisorption of pyridine. The dehydration of 2-propanol and cracking of cumene follow first-order kinetics. The dehydration of propanol on alumina and chromia–alumina catalysts is a structure-insensitive reaction independent of the surface area but related to the surface acid density. The cracking of cumene is a structure-sensitive reaction depending on both the extent of the surface and the number of acid sites.